Association between insulin resistance and aspirin or clopidogrel resistance in Chinese patients with recent ischemic stroke/TIA. (4th May 2021) - Jia, Weili; Jia, Qian; Zhang, Yumei; Zhao, Xingquan; Wang, Yongjun
ABSTRACT: Objective : This study aims to discover whether insulin resistance is an independent predictor for antiplatelet drug resistance in patients with ischemic cerebrovascular disease. Methods : This study used a prospective cohort method. Patients diagnosed as minor ischemic stroke or transient ischemic attack (TIA) were enrolled successively. All patients have been administrated aspirin and/or clopidogrel and were tested for fasting glucose and insulin and platelet aggregation inhibition tests which was detected by light transmission aggregometry (LTA). The maximum platelet aggregation rate (AA) of ≥20% or the maximum platelet aggregation rate (ADP) of ≥50% was defined as antiplatelet drug resistance. Multivariable logistic regression was performed to estimate the association between HOMA-IR and antiplatelet drug resistance. Results : This study recruited successively 237 patients with mild-to-moderate ischemic stroke or TIA in Beijing Tiantan Hospital from 2018 to 2019. Of them 60 cases were recognized as having insulin resistance. There are 46 patients in insulin resistance group (76.7%) developed antiplatelet drug resistance, which was significantly more frequent than patients without insulin resistance (35%, P < 0.0001). Insulin resistance was an independent risk factor for antiplatelet drug resistance in patients with recent ischemic stroke/TIA after adjusted for confounding factors (Odds Ratio 5.281; 95%CI, 2.15 to 13.01, P < 0.0001). Conclusions : Insulin resistance was an independent predictor for development of antiplatelet drug resistance in patients with recent minor ischemic stroke or TIA. More attention should be paid to recognize these patients and antithrombotic effect should be monitored when antiplatelet drugs were applied to these patients.